The Effects Of Artificial Illumination On The Display Behaviour Of The Firefly Pteroptyx tener Olivier (Coleoptera: Lampyridae) - Khoo,, Veronica Swee Imm (2018)
A study on effects of artificial illumination on the Pteroptyx tener Olivier was carried out at Selangor River, Selangor. Studies in the field involved the use of digital night photography, and short and long term exposure to light from a 400W spotlight shining towards the congregating fireflies at the study site. A control site had no artificial light exposure. Short term studies involved exposure of light for 30- minute intervals. The second short term study included short 1-minute intervals of darkness for a total of 3 minutes to allow recovery. Short term exposure to artificial lights had a significant short term effect on flashing behaviour, but recovery took place over time. Continuous illumination for three nights (long term exposure) resulted in a significant long term effect.